(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Palayam was ruled by a king and was a territory roughly equal to the modern taluks. A set number of villages was assigned to a Palayakkarar, the person in charge of the Palayam. As part of his duty, he had to help his lord in war and provide him an annual tribute. Wilson defines a "palayakkarar" as a small-time chieftain in the southern regions of India, particularly in Karnataka and the Tamil area, which mostly occupied hill and forest terrain. They were expected to honor and serve the paramount state. Effectively overseeing the Palayams until the Company’s power in Tamil Country was cemented in 1801, the Palayakkarars. The Palayakkarars’ capacity for independent action was impacted by the policies of both the Company and the Nawab. As a result, they rebelled and challenged the political power of the central forces. Southern Tamil Country experienced multiple battles and revolutions as a result. The Nawab and the Company mercilessly put an end to these uprisings and also employed the Carnatic payanghat to subjugate the Palayams. These Palayams were eventually included into the Company administration at the beginning of the nineteenth century. This study describes the history of the Palayams in the Southern Tamil Country.